Understanding Performance Limiting Interfacial Recombination in pin Perovskite Solar Cells. Issue 12 (9th February 2022) - Warby, Jonathan; Zu, Fengshuo; Zeiske, Stefan; Gutierrez‐Partida, Emilio; Frohloff, Lennart; Kahmann, Simon; Frohna, Kyle; Mosconi, Edoardo; Radicchi, Eros; Lang, Felix; Shah, Sahil; Peña‐Camargo, Francisco; et al.
Abstract: Perovskite semiconductors are an attractive option to overcome the limitations of established silicon based photovoltaic (PV) technologies due to their exceptional opto‐electronic properties and their successful integration into multijunction cells. However, the performance of single‐ and multijunction cells is largely limited by significant nonradiative recombination at the perovskite/organic electron transport layer junctions. In this work, the cause of interfacial recombination at the perovskite/C60 interface is revealed via a combination of photoluminescence, photoelectron spectroscopy, and first‐principle numerical simulations. It is found that the most significant contribution to the total C60 ‐induced recombination loss occurs within the first monolayer of C60, rather than in the bulk of C60 or at the perovskite surface. The experiments show that the C60 molecules act as deep trap states when in direct contact with the perovskite. It is further demonstrated that by reducing the surface coverage of C60, the radiative efficiency of the bare perovskite layer can be retained. The findings of this work pave the way toward overcoming one of the most critical remaining performance losses in perovskite solar cells. Abstract : Nonradiative recombination induced by C60 is limiting the performance of pin type perovskite solar cells and remains poorly understood. In this manuscript, the possible recombination pathways are systematically examined and it is discovered that across‐interface recombination dominates. A point contact strategy is suggested to circumvent the loss, paving the way to improved pin type perovskite solar cells.